EXPERIMENTAL INVESTIGATION AND NONLINEAR ANALYSIS OF POLYMER MEMBERS SUBJECTED TO UNIAXIAL TENSION - Shaker Mahmood, Akram; Yahya Rzayeg, Arz (Anbar Journal of Engineering Sciences, 2008)
An experimental investigation as well as nonlinear analysis is carried out in this paper to study the behavior of polymer members (Epoxy & Polyester) under direct tension. The ANSYS model accounts for nonlinear phenomenon, such as, Tension Softening Material (TSM) and Enhanced Multilinear Isotropic Softening (EMIS) models. The polymer specimens are modeled using PLANE82 element – eight node plane element – eight node plane element, which is capable of simulating the failure behavior of polymer material members. The intention of this paper is thereby to discuss the proposed softening models to validate the complete Stress-Strain and Load-Deflection response of prismatic specimens subjected to uniaxial tension. The outcomes from the verifications of both modeling techniques have shown good agreement with the experimental results obtained from literature.